A Persecuted Church: Roman Catholicism in Early Nineteenth-Century Korea - Finch, Andrew J. (The journal of ecclesiastical history, 2000)
The Catholic Church in Korea dates its foundation from 1784 when Yi Sŭng-hun returned from Beijing where he had been baptised by a member of the resident Catholic mission. He had sought out the Catholic priests at the instigation of Yi Pyok who, in the winter of 1777, had been a member of a meeting of young, reform-minded Shirhak (‘New Learning’) scholars. This meeting had been called to examine scientific, mathematical and religious treatises written by the Jesuits in China. On his return, Yi Sung-hun brought with him books and religious articles which he shared with Yi Pyok, and together they began to evangelise among their friends and neighbours. It was not very long, however, before their activities began to meet with opposition from other Confucian scholars and to arouse the suspicions of the authorities. In 1785 Yi Pyok and other Christians were arrested at a meeting in the house of Kim Pom-u, a member of the chungin class of technical specialists. Those present were given a lecture on proper Confucian conduct and released, apart from Kim Pom-u who was severely beaten and sent into exile where he died from his injuries. Worse was to follow in 1791 with the execution of Yun Chi-ch'ung and his cousin, Kwon Sang-yon, for their refusal to perform the chesa ancestral rites for Yun's dead mother. Nevertheless the Church continued to grow during the 1790s, and its members pressed the bishop of Beijing to send a resident priest. This was achieved in 1795 when a Chinese priest, Fr Chou Wên-mu, arrived in Seoul. Under his ministry, and with the assistance of members of the laity, the Church grew from around 4,000 believers to nearly 10,000 at the outbreak of the Shinyu persecution in 1801. This persecution cost the lives of Fr Chou and at least 300 of the laity, but the Church survived.